Evolution of systemic treatment for hormone-sensitive breast cancer: from sequential use of single agents to the upfront administration of drug combinations - E. N. Imyanitov (Опухоли женской репродуктивной системы, 2016)
Current standards of treatment of endocrine-dependent cancers (breast cancer (BC), prostate cancer) imply sequential use of endocrine therapy and cytotoxic agents: it is believed, that steroid hormone antagonists cease the division of transformed cells and therefore make them resistant to other therapeutic modalities. It is important to recognize that conceptual investigations in this field were carried out dozens of years ago, and often involved relatively non-efficient drugs, imperfect laboratory tests, etc. There are several recent examples of combined use of endocrine therapy and other compounds. The addition of docetaxel (6 cycles) to androgen deprivation resulted in significant improvement of overall survival in men with metastatic prostate cancer. Clinical trial involving the combined use of exemestane and everolimus demonstrated promising results. There are ongoing studies on inhibitors of cycline-dependent kinases. Use of these drugs in the beginning of endocrine therapy may significantly delay resistance to the antagonists of estrogen signaling.